Optimasi Sifat Antifouling Membran Selulosa Asetat/Kitosan dalam Penghilangan PAH dalam Badan Air - Syahrir, Muhammad; Nur Alam, Muhammad; Eka Kartika, Andi; Ilyas, Nita Magfirah (Venn: Journal of Sustainable Innovation on Education, Mathematics and Natural Sciences, 2025)
Water pollution caused by persistent organic compounds such as polycyclic aromatic hydrocarbons (PAHs) has become a serious environmental issue due to their toxicity, recalcitrance, and potential carcinogenic effects. Membrane technology offers an effective solution; however, its performance is often limited by fouling. This study aims to optimize the antifouling properties of cellulose acetate (CA) membranes through chitosan coating (CA/CS) and to evaluate their mechanical, physical, filtration, and antifouling performance. CA membranes were fabricated via the phase inversion method and subsequently coated with chitosan at concentrations of 2%, 5%, and 7%. Characterization included mechanical testing (tensile strength and elastic modulus), physical properties (water contact angle, swelling index, and water permeability), filtration performance (pure water flux and PAH rejection), and antifouling properties (Fouling Deposition Ratio/FDR and Flux Recovery Ratio/FRR). The results showed that chitosan coating enhanced the hydrophilicity, mechanical strength, water permeability, and PAH rejection compared to pristine CA membranes. The optimum performance was achieved at CA/CS 5%, which exhibited the highest tensile strength and elastic modulus, lowest water contact angle, maximum swelling index and permeability, highest flux, PAH rejection up to 88%, and the best antifouling properties (FDR 20% and FRR 82%). In conclusion, chitosan-coated cellulose acetate membranes significantly improved filtration efficiency and fouling resistance. The CA/CS 5% membrane demonstrates strong potential for practical application in the treatment of PAH-contaminated water in an effective and sustainable manner.